Gestión de procesos y calidad del servicio en el Instituto de Educación Superior Tecnológico Público San Lorenzo 2023 - Cuñachi del Aguila, Frank (2024)
The main objective of this final report was to determine the relationship between process management and service quality at the San Lorenzo Public Technological Higher Education Institute, 2023. Working with an applied method at a descriptive and correlational level with a non-experimental design. Taking 120 students as the population, to whom a questionnaire was used to collect data. The results showed that process management is regular (28%), because the institute sometimes monitors the development of the students' learning and professional training processes; as well as sometimes prepares conditions for the management of learning through relevant and timely curricular programming; and sometimes correctly manages educational assets, resources and materials. For its part, the quality of the service is average (27%), since, when students have problems, the Institute follows up and sometimes helps solve the problem; However, the behavior of the Institute's administrative staff and teachers almost never conveys confidence; Also, there is almost never fluid and trusting communication between teachers, administrative staff and students; but teachers never worry about learning, motivate by the subject and encourage student participation; and the staff (managerial, teaching, administrative and service) of the Institute sometimes have a neat appearance. In general, strong correlations are revealed between process management and service quality, supported by a strong positive correlation (0.801). Likewise, a moderate positive correlation was identified between strategic processes (0.733), key processes (0.744) and management processes. support (0.724) with the quality of the service, all of them supported by a statistical significance of 0.000.